Health Trends and Its Implications during the COVID-19 Pandemic in Central Visayas, Philippines - Johnny Jr. Yao; Laurence L Garcia; Ma. Mayla Imelda M Lapa (Asia Pacific Journal of Health Management)
The effects of the Covid-19 pandemic have underscored for the Philippines, in particular, and all countries in general, the importance of a resilient health care system to be able to manage health emergencies and disasters. The study aimed to do a situational analysis of the health sector during the COVID-19 pandemic in the Central Visayas, Philippines. The study collected data from national government agencies in the Philippines. The article identifies gaps in the health care system which may have affected not only COVID-19 outcomes but other health indicators which was highlighted due to the pandemic. The study provides health managers and policymakers information that could be used to promote reforms in the health sector to be able to manage future pandemics and health emergencies both in local and national levels.